RISK FACTORS OF CARDIOVASCULAR DISEASE IN ELDERLY IN GUGUAK KABUPATEN 50 KOTA, WEST SUMATERA, INDONESIA - Debie Anggraini; prima adelin (Universitas Fort De Kock, 2020)
Introduction: Cardiovascular disease (CVD) is a major cause of death and disability worldwide. The most stringent primary CVD screening guidelines in developed countries use absolute CVD risk scores or coronary heart disease, such as Framingham or SCORE (Systematic Coronary Risk Evaluation) there are two types of CVD risk factors namely modifiable risk factors and unmodified risk factors. The aim of the current study is to determine the profil of potentially modifiable and unmodified cardiovascular risk factors. Method: This research consists of 41 elderly people which aged ≥ 60 years in Guguak, Kabupaten 50 Kota, West Sumatera, Indonesia. The data taken is modifiable risk factors consisting of diseases related risk factors including blood pressure categories, lipid profile, central obesity, body mass index and lifestyle related risk factors such as smoking habit. We also take data of unmodified risk factors such as age and gender. The result: this study consists of 41 elderly people which aged ≥ 60 years in Guguak, Kabupaten 50 Kota, West Sumatera, Indonesia. The mean age of elderly were 68±7.64861 years old that consisting of 29.3% men and 70.7% women, 34% of elderly with hypertension, the elderly with hypercholesterolemia 71%, hypertriglyceridemia 41%, and the elderly women with low HDL-C levels were 53%, the elderly men with low HDL-C levels were 92%. Conclusion: There are two types of risk factors CVD, modifiable risk factors and nonmodifiable risk factors. The modifiable risk factors consisting of diseases related risk factors including blood pressure categories, lipid profile, central obesity, body mass index and lifestyle related risk factors such as smoking habit.